Cosmological N-body simulations with a large-scale tidal field. Issue 1 (1st June 2018) - Schmidt, Andreas S; White, Simon D M; Schmidt, Fabian; Stücker, Jens
ABSTRACT: In this paper we carry out anisotropic 'separate universe' simulations by including a large-scale tidal field in the N -body code gadget 4 using an anisotropic expansion factor Aij . We use the code in a pure particle-mesh mode to simulate the evolution of 16 realizations of an initial density field with and without a large-scale tidal field, which are then used to measure the response function describing how the tidal field influences structure formation in the linear and non-linear regimes. Together with the previously measured response to a large scale overdensity, this completely describes the non-linear matter bispectrum in the squeezed limit. We find that, contrary to the density response, the tidal response never significantly exceeds the large-scale perturbation-theory prediction even on non-linear scales for the redshift range we discuss. We develop a simple halo model that takes into account the effect of the tidal field and compare it with our direct measurement from the anisotropic N -body simulations.